1994
DOI: 10.1111/j.1432-1033.1994.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Design of human interleukin‐4 antagonists inhibiting interleukin‐4‐dependent and interleukin‐13‐dependent responses in T‐cells and B‐cells with high efficiency

Abstract: Human interleukin-4 possesses two distinct sites for receptor activation. A signalling site, comprising residues near the C-terminus on helix D, determines the efficacy of interleukin-4 signal transduction without affecting the binding to the interleukin-4 receptor a subunit. A complete antagonist and a series of low-efficacy agonist variants of human interleukin-4 could be generated by introducing combinations of two or three negatively charged aspartic acid residues in this site at positions 121, 124, and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 24 publications
1
96
0
2
Order By: Relevance
“…Although hIL13 and hIL4 are dissimilar at the primary amino acid level, they share similar functions by binding to and signaling through a shared receptor complex (11,12). The shared IL13/4 receptor complex is a heterodimer comprised of an approximate 140-kDa subunit, p140 (13), and an approximate 52-kDa subunit, ␣Ј also termed IL13R␣1 (14 -16).…”
Section: Human Interleukin 13 (Hil13)mentioning
confidence: 99%
“…Although hIL13 and hIL4 are dissimilar at the primary amino acid level, they share similar functions by binding to and signaling through a shared receptor complex (11,12). The shared IL13/4 receptor complex is a heterodimer comprised of an approximate 140-kDa subunit, p140 (13), and an approximate 52-kDa subunit, ␣Ј also termed IL13R␣1 (14 -16).…”
Section: Human Interleukin 13 (Hil13)mentioning
confidence: 99%
“…The IL-4 receptor comprises two chains, the IL-4Ra and the yc [7][8][9][10]. Neither of these two chains binds IL-13 [5], but recent reports have shown that IL-4Ra contributes to the IL-13 receptor [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the structure of this complex has been resolved by x-ray crystallography revealing specific amino acid residues of IL-4 that are involved in the binding of each of the receptor chains (7). Interestingly, preceding this structural knowledge of the IL-4 cytokine/cytokine receptor complex, IL-4 antagonists had been identified through systematic mutagenesis, seeking to abolish binding to the signaling receptor chain ␥C while preserving high affinity binding to the IL-4R␣ chain (8).…”
Section: Interleukin (Il)mentioning
confidence: 99%